Characterization of Pamelo Leaves (Citrus maxima (Burm) Merr) Aceh, Indonesia - Yunus, Ismadi; Putri, Intan Yatima; Hafifah, Hafifah (Journal of Tropical Horticulture, 2018)
Pamelo (Citrus maxima (Burm.) Merr) is one type of orange that is prospectively cultivated in Indonesia. Pamelo in Indonesia is very diverse, as the skin of the fruit is green to red, some are Â with seed and seedless. Pamelo plants have diverse leaves, both in shape, size, lamina and thickness. The various leaf shapes between plants which show below the genetic resources of pamelo plants are numerous and varied. Information about pamelo aceh plants, especially about the character of leaves is still very limited. This information can be used to determine the characteristics of pamelo aceh so that later it will be very useful in classifying and grouping plants. The purpose of this study was to determine the character of the Pamelo Giri Matang leaf in Aceh, Indonesia. The study aims to see the level of diversity of pamelo in the village of Pante Lhong. The study was conducted in the village of Pante Lhong, Peusangan District, Bireuen, Â District, Aceh, Indonesia and at the Laboratory of Agroecotechnology, Faculty of Agriculture, Universitas Malikussaleh, from September to November 2017. The sample plants used were 15, aged between 10 and 25 years. The research was conducted using descriptive method with sampling by purposive sampling method. Observations were carried out quantitatively and qualitatively based on Descriptors for Citrus (PGRI). The results showed that Pamelo Giri Matang Aceh Indonesia was an evergreen plant with an intensity of green to dark leaf color. The average leaf lamina has a length of 14.62 cm and a width of 7.04 cm with an average area of 59.74 cm2. The most commonly found leaf wings are obovate.